Determination of trace silver by high-resolution continuum source flame atomic absorption spectrometry (HR-CS FAAS) after separation/preconcentration on Rhodococcus ruber bacterial biomass. Issue 21 (19th May 2016) - Kariptas, Ergin; Er, Cigdem; Kiray, Esin; Ciftci, Harun
Abstract : In the present study, a preconcentration method was developed by using Rhodococcus ruber bacterial biomass (RrBB) for the determination of silver in various water samples by HR-CS FAAS. Abstract : In the present study, a preconcentration method was developed by using Rhodococcus ruber bacterial biomass (RrBB) for the determination of silver in various water samples by high-resolution continuum source flame atomic absorption spectrometry (HR-CS FAAS). R. ruber is important in many biotransformations and some transformations result in useful commercial processes. RrBB was used for the first time as a sorbent, for bioadsorption of silver in various water samples. The optimum experimental and analytical parameters such as pH of the sample solution, sample volume, flow rate of sample solution and eluent, volume and concentration of the eluent, effect of common matrix ions and capacity of the adsorbent were investigated and optimized. A sample volume of 1000 mL resulted in a preconcentration factor (PF) of 200. Under the optimized conditions, the detection limit and relative standard deviation (RSD) for silver were found to be 1.24 μg L −1 and 3.9% ( n = 7), respectively. The sorbent exhibited excellent stability and its sorption capacity has been found to be 28.4 mg g −1 for silver. The accuracy of the procedure was confirmed by analyzing certified reference materials (NIST SRM 1640a, trace elements in natural water). The developed method was applied successfully for the determination of silver in different water samples.